SIN AND CRIME AS METAPHORS FOR THE REPRESENTATION OF EVIL IN YEATS’S THE COUNTESS CATHLEEN AND PURGATORY - Viana, Maria Rita Drumond (Em Tese, 2009)
This article analyzes the representation of evil in two plays by W. B. Yeats: The countess Cathleen (1892) and Purgatory (1939). Despite revealing different styles, the plays represent a concern with the nature of evil, salvation and damnation of the soul, and the individual’s power against the forces of history.